1974
DOI: 10.1021/j100594a001
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of nitric acid vapor

Abstract: The primary reaction in the photolysis of nitric acid vapor by ultraviolet radiation is " 0 3 + hv -HO + NOz and the primary quantum yield is 1. This article gives experimental evidence in favor of these two conclusions for the wavelengths 200, 255, 290, and 300 nm. The photolysis of nitric acid vapor in laboratory apparatus is subject to several unwanted side reactions, and conditions must be carefully selected to eliminate the effect of such reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…Their pulsed laser photolysis system incorporated atomic resonance fluorescence and LIF detection for the atomic and radical species, respectively. Using excitation at 248 nm they found the OH quantum yield to be f(OH) = 0.95 AE 0.09, in excellent agreement with the earlier result of Johnston et al, [20] and that for the O channel f(O) = 0.031 AE 0.010, which is consistent with the value reported by Margitan and Watson [29] for photolysis at 266 nm. Furthermore, Turnipseed et al [28] observed a slight decrease in f(OH) to 0.90 AE 0.11 at 222 nm, corroborating the previous measurement by Jolly et al [21] Under these excitation conditions the O channel became more efficient, with f(O) = 0.20 AE 0.03.…”
Section: Determination Of Quantum Yieldssupporting
confidence: 89%
See 3 more Smart Citations
“…Their pulsed laser photolysis system incorporated atomic resonance fluorescence and LIF detection for the atomic and radical species, respectively. Using excitation at 248 nm they found the OH quantum yield to be f(OH) = 0.95 AE 0.09, in excellent agreement with the earlier result of Johnston et al, [20] and that for the O channel f(O) = 0.031 AE 0.010, which is consistent with the value reported by Margitan and Watson [29] for photolysis at 266 nm. Furthermore, Turnipseed et al [28] observed a slight decrease in f(OH) to 0.90 AE 0.11 at 222 nm, corroborating the previous measurement by Jolly et al [21] Under these excitation conditions the O channel became more efficient, with f(O) = 0.20 AE 0.03.…”
Section: Determination Of Quantum Yieldssupporting
confidence: 89%
“…A direct method to determine the primary OH quantum yield was later applied by Jolly et al [21] using laser photolysis in combination with resonance absorption measurements of the nascent OH product. At 222 nm a quantum yield of 0.89 AE 0.08 was found, which allowed the authors to concluded that, taking into account possible systematic errors, their result is consistent with that of Johnston et al [20] As a consequence, the OH and NO 2 fragments were considered to be the only products of HNO 3 photolysis. However, the work of Kenner et al [22] cast some doubts on this conclusion.…”
Section: Early Photolysis Studiessupporting
confidence: 77%
See 2 more Smart Citations
“…The observed loss of HNO 3 was eventually explained as being due to the heterogeneous reaction of NO with HNO 3 on the surfaces of the experimental apparatus. 38 However, under the high NO 2 /N 2 O 4 concentrations in those early experiments, it is possible that complexes between NO 2 and/or N 2 O 4 and HNO 3 may have also been present and played a role in the observed enhancement of HNO 3 photolysis.…”
mentioning
confidence: 86%